Mothers’ Knowledge on Toddler Nutritional Status at the Integrated Health Post - Yulia, Revi (Papua Medicine and Health Science, 2025)
Nutritional status is defined as the balance between nutrient intake and the body's nutritional needs. The nutritional status of toddlers is influenced by several direct and indirect factors. Direct factors include toddler food intake and infectious diseases, while indirect factors consist of socioeconomic conditions and limited family knowledge, particularly among mothers, regarding toddler nutritional status. This study aimed to describe mothers’ knowledge on toddler nutritional status at the Pelita 2 Integrated Health Post in Karang Anyar Village, within the working area of the Karang Rejo Public Health Center. This was a descriptive study using a total sampling technique, with 55 respondents selected. Data were collected using a questionnaire that covered respondent characteristics and knowledge-related questions. The results showed that 17 respondents (30.9%) had a good level of knowledge, 32 respondents (58.2%) had a sufficient level, and 6 respondents (10.9%) had a poor level of knowledge. It can be concluded that most mothers had a sufficient level of knowledge regarding toddler nutritional status at the Pelita 2 Integrated Health Post in the Karang Rejo Public Health Center working area, with 32 respondents (58.2%) falling into this category.